The conflict potential of Petrine bureaucracy reform in the mirror of post-Petrine “epoch of palace coups” - D. Yu. Znamenskiy (Вестник университета)
The article considers the reform of the civil service in Russia 1716–1722, and it’s influence on the social processes of post-Peter Russia. The author pays particular attention to the conflict potential of the transformations carried out by Peter I in public service, thereby the most acute conflicts caused by the reforms are distinguished, and their classification and analysis of factors that directly influenced their development are given. The author interprets the events of the first fifth anniversary of the «era of palace coups» in terms of conflict science, analyses the conflicting parties social composition, the logic of their actions, the socio- political results of the confrontation. The initial value gap between the “old” and “new” bureaucracy and a number of problems, have not been solved in the reign of Peter I, are highlighted as key conflict triggers.